DEVELOPMENT OF SCIENCE DIGITAL COMIC ON THE THEME MY AIR POLLUTED TO TRAIN CRITICAL THINKING SKILLS FOR CLASS VII JUNIOR HIGH SCHOOL STUDENTS - Nada Solehah; Lukman Nulhakim; Adi Nestiadi (JURNAL PENA SAINS, 2022)
This study aims to determine the efficiency of science digital comics on the theme of my polluted air to train critical thinking skills of seventh grade junior high school students. The research method used is the research and development (RD) method. By using the 4-D model (Four D Model) proposed by Thiagarajan dkk., (1974) through modifications that are tailored to the needs. The 4-D model is only implemented until the third stage, namely define, design, and development. The instruments used are material expert validation questionnaire sheets, media experts and practitioner experts and student response questionnaire sheets to measure the level of product efficiency. Data analysis is descriptive quantitative and qualitative. The results of this study indicate that the overall validation results of science digital comics on the theme "My Air is Polluted" to train critical thinking skills of seventh grade junior high school students are 92.25%. The results of the efficiency level of IPA digital comic products obtained a value of 82.27% in the "Efficient" category. For further research, it is expected to be able to continue research with a high depth of material and be able to conduct large-scale trials so that research results are maximized.